Ultrasound-guided core needle biopsy compared with open biopsy: a new diagnostic approach to salivary gland enlargement in Sjögren's syndrome?. (17th September 2020) - Zabotti, Alen; Zandonella Callegher, Sara; Lorenzon, Michele; Pegolo, Enrico; Scott, Cathryn A; Tel, Alessandro; Giovannini, Ivan; Robiony, Massimo; Di Loreto, Carla; Zuiani, Chiara; De Vita, Salvatore
Abstract: Objective: Persistent (≥2 months) major salivary gland enlargement in primary SS (pSS) patients is a well-known sign of possible involvement by B cell lymphoma. The study aimed to evaluate the diagnostic accuracy and safety of US-guided core needle biopsy (CNB) of major salivary glands compared with open surgical biopsy. Methods: Prospective pSS patients (cases) with clinically persistent salivary gland enlargement underwent US-guided CNB and were compared with retrospective pSS patients (controls) submitted to open surgical biopsy. The features analysed were pre-biopsy clinical and laboratory findings, adequacy of the material for histology and diagnostic-rendered and biopsy-related complications (reported by the patient with a questionnaire and clinically verified). Results: Thirteen cases underwent US-guided CNB: in nine, biopsy was performed on the parotid gland and in four it was performed on the submandibular gland. Sufficient material was obtained for pathological diagnosis in all samples. The final diagnoses were 5 (38.5%) B cell lymphoma, 1 (7.7%) lymphoepithelial sialadenitis, 4 (30.7%) other sialadenitis (granulomatous consistent with sarcoidosis, IgG4-related disease, chronic sclerosing, diffuse chronic) and 3/13 (23.1%) miscellaneous lesions. Thirteen controls underwent open surgical biopsy of the parotid. In one, inadequate material was obtained, while in 12 (92.3%) the pathologic diagnoses were 4 (33.3%) B cell lymphoma, 2 (16.7%) lymphoepithelial sialadenitis, 4 (33.3%) uncertain lymphoproliferative lesions and 2 (16.7%) miscellaneous lesions. Six cases (46.1%) reported six transient complications and 12/13 (92.3%) controls had 2 persistent and 14 transient complications. Conclusion: US-guided CNB represents a novel, clinically relevant and safe approach for the management of pSS patients with parotid or submandibular persistent enlargement.